Treatment outcome and factors associated with mortality due to malaria in Munini District Hospital, Rwanda in 2016–2017: Retrospective cross-sectional study - Hakizayezu, François; Omolo, Jared; Biracyaza, Emmanuel; Ntaganira, Joseph (Frontiers in Public Health, 2022)
Introduction Malaria is a major public health burden in developing countries despite efforts made by several countries. This disease leads to high morbidity and mortality among Rwandans, particularly in the Southern Province where it was the sixth national cause of morality; at Munini hospital it is the first cause of mortality, but the associated factors remain unknown. In this study, we determined the factors associated with deaths among patients with severe malaria to come up with evidence-based interventions to prevent malaria and its factors. Methods A retrospective cross-sectional study was conducted on malaria patients who were treated at the Munini District Hospital from 2016 to 2017. Data were collected from the hospital records or registers relating to patients who were admitted with severe malaria. The odds ratio was estimated by bivariate logistic regression and multivariate hierarchical regression models for determining the associated factors of deaths. Data were analyzed using STATA/MP Version 14.1 and Epi-info with proportions. Results The study population were mostly women (n = 237, 59.1%), farmers (n = 313, 78.05%), aged 16–30 years (n = 107, 26.68%). Our results indicated that the majority of deaths were women (56.25%). Socio-economic and clinical determinants are important predictors of death among patients with severe malaria. Patients with coma had higher odds of dying (AOR = 7.31, 95% CI :3.33–16.1, p < 0.001) than those who were not. The possibility of mortality increased by almost four times in patients who delayed consultation by a day (AOR = 3.7, 95%CI:1.8–4.1; p < 0.001) compared to those who came in very early. Patients who had severe malaria in the dry season were at a lower risk of mortality (AOR = 0.23, 95%CI:0.08–0.64, p = 0.005) compared to those with severe malaria during the rainy season. Conclusion Lack of health insurance, age of the patient, delayed diagnosis, coma, proximity and access to healthcare services, and weather conditions were the major factors associated with mortality among patients with severe malaria. Comprehensive, long-term, equity-based healthcare interventions and immediate care strategies are recommended.